2016
DOI: 10.4028/www.scientific.net/msf.845.273
|View full text |Cite
|
Sign up to set email alerts
|

Meteoroid, Bolide and Meteorite «Chelyabinsk»

Abstract: This paper presents the brief review of Chelyabinsk group of meteoroid, bolide and meteorite "Chelyabinsk" investigations. Height of the maximum of the main flash of Chelyabinsk bolide is 30 km. Only 1% of meteoroid mass arrived to the Earth surface in the form of meteorites while the most part of meteoroid became dust. During four days the dust had circumnavigated the globe and formed stratospheric dust belt. This new dust belt, located above the Junge aerosol layer, has persisted over at least a three-month … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…There are many light inclusions inside the meteoritic material (Fig. 5a, b), which are apparently a mixture of Fe, Ni metal blebs (Dudorov et al 2016) with some sulphides additions. The size of the light inclusions is ranged from 10 to 100 µm (Fig.…”
Section: Fracture Behaviourmentioning
confidence: 99%
See 3 more Smart Citations
“…There are many light inclusions inside the meteoritic material (Fig. 5a, b), which are apparently a mixture of Fe, Ni metal blebs (Dudorov et al 2016) with some sulphides additions. The size of the light inclusions is ranged from 10 to 100 µm (Fig.…”
Section: Fracture Behaviourmentioning
confidence: 99%
“…5c). It has been shown that the light inclusions are metallic phase consisting mainly of Fe and Ni (Dudorov et al 2016). Brittle cracks propagated into Fe, Ni blebs which previously had been fracture free.…”
Section: Deformation and Fracture Behaviour Of The Chelyabinsk Chondritementioning
confidence: 99%
See 2 more Smart Citations
“…Note that the employed model does not involve the process of SB fragmentation (Barri 2010;Stulov & Titova 2001;Dudorov et al 2015), since the initial dimensions of the SB are taken to be quite significant (from 50 to 200 metres) as well as moderate velocities, when most of the SB remains intact, despite extreme external influences. First of all, maximum resistance to fragmentation is characteristic of iron SBs that is associated with the high homogeneity of their internal structure.…”
Section: The Loss Of the Space Body Mass And The Heatmentioning
confidence: 99%